Pentingnya Penerapan Etika Bisnis Pada Perusahaan Di Indoneisa - Ire Puspa Wardhani (JAKSTIK Journal, 2008)
Ethics in business within the enterprise is essential. Ethics play a role in terms ofManaging all the rights and obligations of employees in the company. Ethics also ensuresthat no employee who did not get justice in the company. The goal is to help everyoneunderstand what is expected by the company to its employees.Code of conduct in companies in the West is already running, and consider an institutionincorporated under the laws themselves. Not so our society. Many companies in Indonesiawhich was not a corporate organization with good management, but rather like a shop.Fortunately, the harm is not clear.An organization can long survive is not shaped by great management, nor by greatpeople, or systems, but built by a strength values. Those values are always stressed to digsomething starting from the bottom.Ethics is the science that deepens the moral standards of personal and moral standards ofsociety. Ethics questioned how the standards applied in our lives and whether thestandards that made sense or not. Reasonable standard that is supported by reasoningthat whether good or bad. Ethics is also a review of moral standards, moral standardsinspection process or the public to determine whether these standards make sense or notto apply in concrete situations and problems. The ultimate goal is to develop the moralstandards of building our sense of moral standards that make sense to adopted. Explicitpurpose of ethics is to determine the correct standard or supported by good reasoning,and thus try to reach conclusions about the ethics of a true moral right and wrong, andmoral good and evil.Business ethics is a specialized study of moral right and wrong as applied to the standardin policies, institutions, and business conduct. and how the standards were implementedinto the system and organization of modern society which used to produce and distributegoods and services and applies to people who are in the organization.Keywords: Business ethics, corporate culture, corporate